Análise-multitemporal da paisagem, potecialidades e fragilidades sob a ótica do uso e ocupação: destaque para as terras da Alta Bacia do Rio Taboco-MS - Santana, Waleska Souza Carvalho [UNESP] (2015)
The Upper Basin Taboco River has an area of 109.42 km2, in a perimeter of 64.09 km, central-western portion of Mato Grosso do Sul, city of Corguinho MS. The Taboco river is ingrown on the surface of Maracaju plateau - Campo Grande, in the Sedimentary Basin of Paraná. The objective of this research is to analyze the dynamics of anthropogenic changes, therewith propose a better way to use and occupation, through a spatial rearrangement of territorial planning of Upper River Basin Taboco, with the support of geoprocessing techniques. The methodological theoretical basis adopted is the systemic analysis, through the mesh integrated the physical and anthropic medium, organizing a database, through geographic surveys and cartographic bases, by creating thematic maps and using secondary basis, from relief maps, natural and potential weaknesses to synthesis maps of use and occupation of 1984, 2004, 2013, environmental zoning and territorial planning. The results show a close relationship between the landforms specially the slope, with the use and occupation through the pastures, the main focus in the region, activity that reigns economic development, also contributes to the main environmental problems, as excessive deforestation of native vegetation of Upper Basin, around 60% of the area is suitable for pastures. For this reason, there is a need to propose solutions to improve the relationship between man and environment. The proposal follows a contextualization based on environmental legislation, weaknesses and natural potentialities of Upper Basin, dividing the areas in: restricted - likely to permanent preservation; productive - destined for use and occupation with the extensive livestock cattle; and divergent of use, areas with conflicts of use, associated with environmental issues